Hydrochemical Investigation and Water Quality Index of Groundwater in the Abu Ghraib District, Western Baghdad Governorate, Iraq - Al -Rubaie, Zainab.J.; Al-Kubaisi, Qusai.Y. (Iraqi Journal of Science, 2025)
The groundwater quality in the Abu Ghraib area of Baghdad governorate was estimated using a water quality index. Abu Ghraib area is located between latitudes (33° 10' 5" - 33° 22' 4" N) and longitudes (44° 1' 0" - 44° 13' 7" E) where twenty samples sixteen from groundwater, three from the Main drain, and one channel from the Euphrates River were collected and analysed between September 2023 and April 2024 for physical and chemical data. Which include TDS, pH, EC, Cation and anion. The sampled water was  neutral to slightly alkaline based on pH results. Groundwater samples are categorized as fresh to mildly salted according to TDS classifications. Every sample water is excessively mineralized according to Ec.. By applying the Kurlolov equation, it has been found that most water samples are of CaSO4 type, and the other samples range between NaSO4, NaCl, and CaCl. When using the Durov classification, it was found that the samples were chloride-sulphate. The water quality in the study area for two period are categorized as good water (Ch) and poor water for (W16), while the remaining samples are classified as very poor water to unsuitable  for ueses water due to high values of the calculated WQI values. It can be used for agricultural activity, with the except of W2 and W7, although it is good for livestock, building, and irrigation .